Burnout Syndrome on Care Givers and The Fulfillment Needs of Care in The Post Stroke Patients at Physiotherapy Outpatient Ward in RST DR. Soepraoen - setyoadi, Setyoadi; Wihastuti, Titin Andri (University of Muhammadiyah Malang, 2018)
Caregivers in post-stroke patients reported physical and emotional symptoms of exhaustion. These symptoms lead to burnout syndrome which may result in decrease in productivity of caregivers in fulfilling the needs of post-stroke patients who were treated. The aim of this study was to identify the relationship between caregiver’s burnout syndrome and fulfillness of care needs in post-stroke patients. Design of this study was quantitative analitic correlation with cross sectional. The participants were 20 post-stroke patients and their caregiver that came to Physiotherapy Unit at dr. Soepraoen Hospital during the study period. The data were taken using 3 questionnaires, modified MBI (Maslach Burnout Inventory), care needs of post-stroke patients questionnaires and Barthel Index. The results from Spearman Rank test with 0.05 significance indicated a relationship between caregiver’s burnout syndrome and fulfillness of care needs in post-stroke elderly, the more severe burnout syndrome experienced by the caregivers, the more care needs of post-stroke patients are not fulfilled. Researchers provide suggestions for the next research to use more respondent and different methods to get different results.